Food consumption and expenditures in Singapore: implications to Malaysia’s agricultural exports - Tey, Yeong Sheng; Darham, Suryani; Alias, Emmy Farha; Ismail, Illisriyani (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
Imports are the only source of food supply to Singapore. Such condition offers a very attractive proposition for agricultural oriented countries. The dependence on type of food imports is determined by consumer demand. This study intends to do an exploratory study on the current conditions of Singaporean food consumption and expenditures with implications on Malaysia as an important agricultural exporting country to Singapore. It is identified that Singaporean consumers tend to demand for high quality poultry, pork, seafood, vegetables, and fruits in future, particularly in response to income growth. At the mean time, Malaysia is seemingly rich in the production of these food commodities and commits to exports for the excess of the supplies. While facing competition from various countries, Malaysia still possesses various competitive advantages over the other countries.